Ecscw 2005
DOI: 10.1007/1-4020-4023-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Managing Currents of Work: Multi-tasking Among Multiple Collaborations

Abstract: Abstract. This research reports on a study of the interplay between multi-tasking and collaborative work. We conducted an ethnographic study in two different companies where we observed the experiences and practices of thirty-six information workers. We observed that people continually switch between different collaborative contexts throughout their day. We refer to activities that are thematically connected as working spheres. We discovered that to multi-task and cope with the resulting fragmentation of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
86
0

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 19 publications
3
86
0
Order By: Relevance
“…However, mediation of awareness always happens in a social context that gives meaning to it and relates to multiple social networks [16]. Empirical investigation has shown that we are continuously moving across different collaboration spheres that compete to get our attention [9]. While this study focuses mainly on the working environment, an initial study that we have conducted with a group of exchange students has pointed out similar issues also in connection to awareness mediation.…”
Section: Introductionmentioning
confidence: 92%
“…However, mediation of awareness always happens in a social context that gives meaning to it and relates to multiple social networks [16]. Empirical investigation has shown that we are continuously moving across different collaboration spheres that compete to get our attention [9]. While this study focuses mainly on the working environment, an initial study that we have conducted with a group of exchange students has pointed out similar issues also in connection to awareness mediation.…”
Section: Introductionmentioning
confidence: 92%
“…Many studies have been conducted in the last forty years to understand how knowledge workers divide their time and efforts among several projects and initiatives at the workplace [2,3,5]. Some of these studies have shown that activities performed by information workers are varied, fragmented, and brief, which forces them to focus on each activity for a short period of time [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have shown that activities performed by information workers are varied, fragmented, and brief, which forces them to focus on each activity for a short period of time [5]. This reality makes information workers to engage in explicit efforts to keep control over their commitments, and use strategies to organize, prioritize and focus on what they have and want to do [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased availability of such media communication media and the increasingly continuous connectivity of individuals can have fundamental impact on the way we work together with colleagues, or the way we socialize with friends and family. Individuals can initiate contacts opportunistically and with great ease, which at the receiving end creates the problem of managing one's availability for communication [1][2][3]. This need is manifested at work, where one has to avoid interrupting or being interrupted for the sake of productivity, reduced stress, and even for avoiding erroneous action; it is also manifested at leisure when individuals need to secure moments of leisure, relaxation, or private enjoyment alone or with family and friends [4][5][6].…”
mentioning
confidence: 99%